THE ROLE OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE, GREEN ACCOUNTING, ENVIRONMENTAL PERFORMANCE ON COMPANY VALUE WITH PROFITABILITY AS A MODERATING VARIABLE (STUDY ON MINING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2018-2023) - Wanda Aulia Rosyidah Rosyidah; Hadiah Fitriyah (Antis Publisher, 2025)
Objective: The purpose of this research is to determine whether the profitability variable can moderate the Corporate Social Responsibility Disclosure, Green Accounting, and Environmental Performance variables on company value. Method: The population in this study were mining sector companies for the period 2018–2023. The sample was selected using the purposive sampling method, and the data analysis technique used was the outer model to test the validity and reliability of the data and the inner model to test the hypothesis using the SmartPLS version 3.0 analysis tool. Result: The results of this study indicate that Corporate Social Responsibility Disclosure, Green Accounting, and Environmental Performance have an effect on company value. The profitability variable is able to moderate Corporate Social Responsibility Disclosure, Green Accounting, and Environmental Performance on company value. Novelty: The novelty of this study lies in the integration of profitability as a moderating variable in examining the relationship between Corporate Social Responsibility Disclosure, Green Accounting, and Environmental Performance on company value within mining sector companies, providing new empirical insights into how profitability strengthens the effect of sustainability practices on firm value.